Isolation and characterization of 10 microsatellite loci in the common dormouse Muscardinus avellanarius - Naim, D.M.D.; Kemp, Stephen J.; Telfer, S.; Watts, P.C. (Wiley, 2009)
To assess the level and spatial pattern of genetic diversity of the common dormouse, Muscardinus avellanarius, we developed polymorphic microsatellite loci from partial genomic libraries enriched for microsatellite motifs. Ten dinucleotide polymorphic microsatellites were isolated and levels of genetic diversity were assessed in 139 individuals from Bontuchel, (Denbighshire, Wales). We observed high levels of heterozygosity (mean HO = 0.792 ± 0.077; mean HE = 0.730 ± 0.084) and a large number of alleles (Na = 6–17). There was no evidence of deviations from Hardy–Weinberg conditions, or genotypic disequilibrium between any pairs of loci. This is the first description of microsatellite primers from a common dormouse and these loci are currently being used to quantify dormouse spatial genetic structure.